EFFECT OF LIV-52 ON VANADYL SULPHATE - BIHARDWAJ, SHAKTI; MATHUR, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
An Ayurvedic medicine Liv-52 was studied as a prophylactic agent against Vanadium induced toxicity in rats by administration of Vanadyl sulphate at a dose of 40 mg/kg (I.P.) Once only, Blood biochemical parameters also showed disturbed RBC, WBC, Hb% after vanadium exposure. Activities of SGOT and SGPT increased significantly. Liv-52 primed rats, however, exhibited comparatively less marked toxic effects.